DOCUMENT SERVING THE CONCLUSION OF A CONTRACT AND CONVEYANCE OF A RIGHT: INTERWEAVING OF THE ROMAN AND GREEK LEGAL TRADITIONS IN BYZANTINE PRIVATE LAW - Ilić, Tamara (Pravni zapisi, 2022)
The purchase contract, often referred to as sale and purchase (πρᾶσις καὶἀγορασία) as an illustration of its twofold nature derived from the Roman legaltradition, or simply as sale (πρᾶσις), is suitable for analyzing different legal issues. Inlight of typical Byzantine document named πρατήριον ἔγγραφον, we aim to definethe nature of purchase contract in this medieval legal system. Diplomatic formulaecontain data about consensus of contractual parties, as well as the fact that adocument was drafted “for security”, which raises the question of solemnity of thiscontract. The role the deed has is also discussed in the paper, as in some cases it isuncertain whether the composition and delivery of the document also implied thepassing of title. Applied methodological approach takes into account the linguisticinterpretation of documentary clauses and legal provisions in codes, and relies oncomparative-historical method.
Keywords: Byzantine law; ancient Greek law; Roman law; ownership; Byzantine documentary practice; traditio ficta